(untitled) (Revista Direito em Debate, 2022)
The article discusses the economic costs of criminal drug policy and its consequent increase in Brazilian incarceration. For this, it develops the study based on data from the state of Paraná. The theme is relevant because the issue requires the attention of government authorities, researchers and society in the search for results to minimize the effects of policies that result in the expansion of public and private spending and the increase in the sense of fear and urban insecurity. The article suggests, based on bibliographic research, empirical observation and professional experience, using the hypothetical-deductive method, that actions aimed at reducing crime, coordinated only through public security agencies, are palliative and lack effectiveness, especially regarding crime derived from drug use and trafficking. It concludes that overcoming the problem depends on changing the punitive paradigm that orbits around penalizing socio-legal practices, and prioritizing decriminalizing political-institutional alternatives that aim at the peaceful, restorative and non-incarcerative resolution of drug-related problems.